Mapping Green Practices in the Hospitality Industry: A Bibliometric and Content Analysis of Scopus-Indexed Literature - Fandy Yones Latuni; Lawren Julio Rumokoy; Christoffel M. O. Mintardjo; Fitty Valdi Arie (CV Edujavare Publishing, 2026)
The hospitality industry contributes significantly to the global economy, but its operational activities generate environmental impacts, such as energy consumption, water use, waste, and carbon emissions. This study aims to map research trends related to green practices, green hotels, and sustainable hotels, and to identify dominant themes and literature gaps through a combination of bibliometric and content analysis. This research method uses a qualitative approach through a literature review, with bibliometric data obtained from 959 documents indexed by Scopus, analyzed using VOSviewer through network visualization, overlay, and density visualization. Next, content analysis was conducted on 40 selected articles based on topic relevance and abstract clarity. The bibliometric results show significant growth in publications in the 2020–2025 period, with key clusters related to employee behavior, consumer behavior, green human resource management (GHRM), corporate social responsibility (CSR), organizational performance, and post-pandemic sustainability. The content analysis identified three main categories in the implementation of green practices: human factors, organizational factors, and technology and innovation factors. This study confirms that the implementation of green practices is a multidimensional phenomenon that requires an integrative approach. These findings provide theoretical, practical, and methodological contributions, and offer a future research agenda that emphasizes the integration of people, organizations, and technology, digitalization, and the implementation of smart hospitality.